An Overview on Diabetic Neuropathy - Singh, Ujjawal; Sharma, Ramsha; Kumar, Ranjeet (Current Diabetes Reviews, 2025)
The term “Diabetic neuropathy” refers to a collection of clinical and subclinical symptoms caused by problems with the peripheral nervous system. Diabetes, which affects approximately 381 million people worldwide, is the source of dysfunction due to the emergence of microvascular complications. It is anticipated that in the next ten years, Diabetic neuropathy will manifest in about 50% of patients who are currently diagnosed with diabetes. Clinical diagnosis can be established by getting a thorough patient history and exploring the symptoms to rule out alternative causes. Although distal symmetrical polyneuropathy, or just, is the most common and well-researched variant of the disorder, this review will concentrate on it. The multifactorial pathogenesis is linked to various inflammatory, vascular, metabolic, and neurodegenerative illnesses. The three fundamental molecular alterations that lead to the development of diabetic neuropathic pain are oxidative stress, endothelial dysfunction, and chronic inflammation. These three elements are crucial in the development of polyneuropathy because their combination might result in direct axonal damage and nerve ischemia. The purpose of this article was to provide a narrative review of diabetic neuropathy. We provide an overview of the most recent data on biomarkers, the pathogenesis of the illness, the most recent epidemiology of diabetic neuropathy, and the existing screening and diagnosis outcome measures used in both clinical and research contexts.
Keywords: endothelial dysfunction